GESTÃO ESTRATÉGICA DE INOVAÇÃO TECNOLÓGICA E EMPREENDEDORISMO PROJETOS DE P&D PESQUISA E DESENVOLVIMENTO DAS EMPRESAS DISTRIBUIDORAS DE ENERGIA ELÉTRICA CASO AMPLA ENERGIA E SERVIÇOS S.A. - Barreto Neto, Acacio (2008)
The objective of this case study is to analyze and verify the management of innovation in an electric power distributing company in Brazil, by looking at their research and development programs and the generation of ideas, placing them in the context of the present market for electric power, which transform knowledge into business. Specifically, the model for Ampla Energia e Serviços S A. will be studied and the results of projects in which generate useful prototypes, but do not complete the cycle in the chain of innovation and reach the commercialization phase. The case study uses a qualitative research approach (action), because of the possibility that explicit information may be difficult to identify, and also a brief quantitative evaluation showing the results of the last ten years about innovation in the electric power sector and Ampla Energia e Serviços S A. The perceptions of the agents involved in this productive arrangement: electric power distributors, universities, research centers, technology-based companies and researchers are identified and analyzed; both with regard to the barriers as well as the gaps existing today in various stages of the innovation chain, but focused on the post-project (commercialization) stage. The study hopes to shed some light on the process of management of technological innovation of companies, both in terms of integrated planning in the medium and long run, with emphasis on the interests and these strategies established under corporate governance. It s possible to help research and development managers to make decisions with regard to a balanced selection of projects for R&D portfolios (incremental and discontinuous) and further guide the model of integration of the program of ideas and solutions with the R&D program, on the point of view from the commercial and marketing for new products non regulated.